Desmin detection by facile prepared carbon quantum dots for early screening of colorectal cancer. Issue 5 (February 2017) - Li, Chang-feng; Yan, Zhen-kun; Chen, Li-bo; Jin, Jing-peng; Li, Dan-dan
Abstract : Abstract: Th aim of this study was to develop a new facile chemical method for early screening of colorectal cancer. The -C(O)OH groups modified Carbon Quantum Dots (CQDs) were prepared by an facile innovative route of acid attacking on carbon nanotubes (CNTs). The -C(O)OH groups were further transported into -C(O)Cl groups by SOCl2 treating. The obtained ClCQDs were conjugated onto the anti-Desmin, which were applied for testing the Desmin concentration in serum by using linearly fitted relationship with photoluminescence (PL) intensity. The obtained carbon quantum dots are quasispherical graphite nanocrystals with photoluminescence at about 455 nm. The Desmin with concentration of 1 ng/mL can lead to a decrease of PL intensity for anti-Desmin conjugated CQDs with good linearity. This assay had good specificity for Desmin with in interferential substances of immunoglobulin G (IgG), alpha fetoprotein (AFP), and carcinoembryoic antigen (CEA). A new facile acid attack method was developed to prepare ClCQDs, which could conjugate onto the anti-Desmin for detection of Desmin in serum with high sensitivity and specificity. As the detection limit is lower than 1 ng/ mL, this work provides a promising strategy for the evaluation of colorectal cancer risk with low cost and excellent sensing performance.